3-Deoxy-D-arabino-heptulosonate 7-phosphate synthase as the gatekeeper of plant aromatic natural product biosynthesis. (June 2022) - Yokoyama, Ryo; Kleven, Bailey; Gupta, Anika; Wang, Yuer; Maeda, Hiroshi A.
Abstract: The shikimate pathway connects the central carbon metabolism with the biosynthesis of aromatic amino acids—l -tyrosine, l -phenylalanine, and l -tryptophan—which play indispensable roles as precursors of numerous aromatic phytochemicals. Despite the importance of the shikimate pathway-derived products for both plant physiology and human society, the regulatory mechanism of the shikimate pathway remains elusive. This review summarizes the recent progress and current understanding on the plant 3-deoxy-D- arabino -heptulosonate 7-phosphate synthase (DAHP synthase or DHS) enzymes that catalyze the committed reaction of the shikimate pathway. We particularly focus on how the DHS activity is regulated in plants in comparison to those of microbes and discuss potential roles of DHS as the critical gatekeeper for the production of plant aromatic compounds.